Marketing Strategies of Multinational Enterprises and Nongovernmental Organization (International Journal of Innovative Research in Engineering & Management, 2021)
Business is not a simple for any one as there are many  companies exited in the market in various area. One need to  prepare their preparation and plans carefully so that they may  compete in highly turbulent market and generate profit for  their organisation. The current research has been prepared to  figure out the difference and similarities between the  marketing strategy of an organisation who are engaged into  pure industrial operations and a non-profit organisation. The  marketing tactics are important elements which may be  determined in preparation before start the real activity. The  basic aim of an NGO is to being revolutionary changes in the  society as well as in mind of people but they need fund to  carried out their activities and they have to options for this,  first generate their own money through some business  activities and second solely depends upon the fund received  from other organisation. The future consequence of this  research is to discover the answer and comparison as well for  marketing planning of NGO in comparison to pure industrial organisation.
Keywords: Nongovernmental Organisation; Business; Industry; Philanthropist